Understanding and Managing Skilled and Creative Labour: The Theory Behind China’s Economic Miracle (World Marxist Review, 2025)
The world of Chinese Marxism is little known to Western Marxist scholars, let alone the general Anglophone reading public. This book is therefore of double importance. First, it serves as an introduction to Chinese economic thinking, for anyone wanting to study, with an open mind, China’s economic successes and the principles that underlie it. Second, it will introduce Western Marxists to Chinese Marxist thinking.Marxist economic analysis is integral to the policies underlying China’s success. This may not be apparent to readers whose contact with Chinese economics is confined to University departments where the neoclassical canon prevails. However, Western ‘standard economics’ is by no means the basis of Chinese political decision-making. Marxist thinking plays a major role in Chinese policy and debates initiated by Marxists are at the forefront of the choices facing policy-makers, as this fascinating book shows.For this very reason, the book is highly practical. In order to confront the complexity and uniqueness of China’s economic miracle, the authors have developed Marxism in exciting and innovative ways.The book thus provides an unparalleled introduction to the dynamism and breadth of the issues facing Chinese Marxists and Chinese economists in general. It extends the boundaries of Marxist political economy in creative and productive directions which are of world-wide importance, not in China alone.